The assessment of the effect of gaze direction instruction on the stabilisation during artistic gymnastic landing - Pavlasová, K.; Bizovská, L.; Rupcík, L.; Farana, R.; Janura, M. (European Journal of Sport Science, 2026)
The aim of this study was to assess the effect of gaze direction instruction on postural stabilisation and muscle activity during landings after various motor tasks in artistic gymnastics. Eighteen female gymnasts (aged 14.0 ± 2.7 years) performed four different landing tasks: drop landing, backward somersault, forward somersault (SF) and a backward acrobatic series (AS). Gaze was directed either downward or straight ahead during landings. Muscle activity was recorded from six lower limb muscles and postural stabilisation was assessed using dynamic stability indices and time to stabilisation. Results showed a significant effect of motor task on muscle activity and stabilisation, with AS and SF presenting higher stabilisation demands. Gaze direction instruction had limited influence on muscle activation patterns and stabilisation, with limited manifestation in dynamic stability indices. Interactions between gaze and motor task were significant only for sagittal dynamic stability in longer time intervals. These findings suggest that motor task complexity primarily governs landing stabilisation, whereas gaze direction plays a minor role in lower limb muscle activity.